Pengaruh Perkembangan Teknologi Informasi Komunikasi Terhadap Minat Baca Peserta Didik Di Perpustakaan Universitas Muhammadiyah Sumatera Utara - Miftah Rizki Ananda; Zaitul Ummi; Zaidan Zuhdi Batubara (Kitabah: Jurnal Pendidikan Sosial Humaniora, 2023)
The purpose of this study is to describe the development of information and communication technology on students' reading interest at Muhammadiyah University, North Sumatra. The method used is descriptive analysis where the design uses a quantitative design. The instrument used during the research was a questionnaire to find out which students were involved during data collection. It was found that there is a strong influence between information and development technology on students' interest in reading in the library, which means that the growing development of information and communication technology reduces students' interest in reading in the library